Backstepping and sliding-mode methods for stabilizing an underactuated X4-AUV - Zainah, Md. Zain; Nurfadzillah, Harun; Nur Natasha, Hanipah; Norhafizah, Md. Zain (UTeM, 2017)
In this paper, we are interested principally in dynamic modelling of an autonomous underwater vehicle (X4-AUV) while taking into account the high order nonholonomic constraints in order to develop a new control scheme as well as the various physical phenomena, which can influence the dynamic of a swimming structure. We deal with the design of two controllers, based on backstepping and sliding-mode control techniques to stabilize altitude and attitude of an underactuated X4-AUV. The designed controllers are: full backstepping control for attitude and altitude control, and partially slidingmode control for attitude combine with altitude backstepping control. Some numerical simulations are conducted to demonstrate the effectiveness of the proposed controllers.